Experimental Investigation on Adsorption of Methyl orange Using eggshells as adsorbent Surface - Al Nasir, Hareer A.; Mohammed, Suhad S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The role of residues in the adsorption process for removing contaminants from their aqueous solution was highlighted in this study. The adsorption capacity of eggshells were used to remove the methyl orange dye from its aqueous solution. The highest dye adsorption was found to range between (62.30% to 62.33%). The results of using adsorption isotherms (Freundlich, Langmuir, and Temkin) have been revealed that the Freundlich model was followed and that the Langmuir model did not match, as well as the partial applicability of Temkin's model at temperatures (298,308,318) K. The process of adsorption is a physical one. Three kinetic models of the adsorption process were also used, with the results demonstrating the applicability of the pseudo-second-order model. In this study, the thermodynamic functions were estimated using the value of the enthalpy ΔH°, which was negative and equal to (-4.7685 KJ/mole), The process was discovered to be exothermic, and the entropy ΔS° value was also negative, equaling (- 11.5100 J/mole.K), indicating a decrease in the randomness of adsorption when added to the Gibbs free energy ΔG°, indicating that the reaction occurred spontaneously.